Using WhatsApp in tourism ESP classes: A linguistic analysis of the language used, and grammatical mistakes made - Calvo Benzies, Yolanda Joy (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this paper, we will analyse the language used by a group of Tourism ESP students on WhatsApp. The data will be analysed from different perspectives: a) the grammatical mistakes made, and b) the students´ degree of adaptation to the most common linguistic features in text messages. The results indicate that these students continue to make some basic grammatical mistakes they should have already overcome. Moreover, many linguistic features of text messages were encountered in their interventions such as punctuation overuse and deletion and overuse of sounds. Finally, they insert many emojis in their messages to express different meanings.